Pembatalan Kewenangan Dewan Pengawas Komisi Pemberantasan Korupsi Dalam Hal Pemberian Izin Penyadapan, Penggeledahan Dan Penyitaan Pada Putusan Mahkamah Konstitusi Nomor 70/ PUU-XVII/2019 Dalam Perspektif Efektifitas Hukum - Sony Aldianto; Burhanudin Burhanudin; Tresia Elda (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The main problem in this study is that, the position of the Supervisory Board of the Corruption Eradication Commission after the authority in granting wiretapping, search and seizure permits was canceled by the Constitutional Court in the perspective of the effectiveness of the law and the criminal justice system. This study aims to make everyone understand the position and urgency of the KPK Supervisory Board after the Constitutional Court Decision Number 70/PUU-XVII/2019 in the concept of legal effectiveness and the criminal justice system in Indonesia. The results of this study indicate that regarding the judge's considerations, that the Supervisory Board of the Corruption Eradication commission in granting wiretapping, search and confiscation permits is a real form of overlapping authority of pro justitia. The KPK Supervisory Board is not a law enforcement officer, so it is not in accordance with the effectiveness of the law in terms of law enforcement factors, community factors and legal factors, therefore is not included in the components of the criminal justice system and violates the concept of the criminal justice system.